Use of 3-PG model to predict eucalypt biomass in Jalisco, México - Guevara-Escobar, Aurelio; Cervantes-Jiménez, Mónica; Suzán-Azpiri, Humberto (Instituto de Ecología, A.C., 2020)
Biomass modeling in forest plantations is an alternative to quantify carbon stored in vegetation. Predictions are important for management decisions or efforts to mitigate climate change. An important relationship is that of soil moisture (q) with biomass. The 3-PG model was used to predict biomass production in different scenarios of q in a Eucalyptus globulus plantation in subtropical climate. From 2007 to 2009, we measured q in the 0 m - 1.8 m soil profile, leaf area index and the diameter at breast height. Precipitation was registered and crop and potential evapotranspiration were estimated for one year based on the water balance, with values of 959 mm, 514.3 mm and 1303 mm, respectively. The predictions of leaf area index and evapotranspiration overestimate observed data. At eight years, biomass was modeled as 165.5 Mg ha-1, of which 23.1 Mg ha-1 is stored in roots and 59.5 Mg ha-1 in aboveground biomass. In conclusion, minimum soil moisture data are necessary to model diameter at breast height and it is desirable to assemble models instead of selecting a single model or using the average of them.